Past, Present and Perspective Methodology for Groundwater Modeling-Based Machine Learning Approaches - Osman A.I.A.; Ahmed A.N.; Huang Y.F.; Kumar P.; Birima A.H.; Sherif M.; Sefelnasr A.; Ebraheemand A.A.; El-Shafie A. (Springer Science and Business Media B.V., 2023)
Machine learning; Numerical methods; Water levels; Ground water level; Groundwater modelling; Hydrological variables; Level model; Machine learning approaches; Meteorological variables; Model method; Model-based OPC; Rapid urbanizations; Water level variations; Groundwater